Case reportGiant aneurysm in medial anterior descending artery: treatment with two endovascular stent grafts on bare metal stent scaffold - Król, Marek; Skwarna, Bartosz; Gałuszka, Grzegorz; Szymański, Radosław; Buszman, Paweł (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
We report a case of a 55-year-old male with a history of coronary artery bypass grafts, who presented with symptoms of unstable angina. The coronary angiography revealed a large aneurysm in the medial segment of the anterior descending artery (LAD), chronic total occlusion of circumflex artery (Cx), and right coronary artery (RCA), occluded LIMA-LAD, and patent grafts Ao-RCA and Ao-Cx. The diameter and length of the aneurysm were 15 mm and 27 mm, respectively. The length of the aneurysm was longer than any commercially available stent graft. The innovatory method of bare metal stent implantation as a basis of construction and stent-in-stent implantation of two stent grafts were performed covering the aneurysm and achieving thrombolysis in myocardial infarction (TIMI) 3 flow in the distal LAD. Unfortunately acute thrombosis was noted 2 h after the first procedure. Immediately aspiration of the thrombus was successfully performed. The control coronary angiography after 3 days showed TIMI 3 flow in the distal LAD. The patient was discharged home without complications and during 16 months of follow-up he remained asymptomatic. The control coronary angiography performed 16 months after the first procedure revealed patent stent grafts in the LAD without restenosis.